Glycemic Dysregulations Are Associated With Worsening Cognitive Function in Older Participants at High Risk of Cardiovascular Disease: Two-Year Follow-up in the PREDIMED-Plus Study - Gómez-Martínez, Carlos; Babio, Nancy; Júlvez, Jordi; Becerra-Tomás, Nerea; Martínez-González, Miguel Á.; Corella, Dolores; Castañer, Olga; Romaguera, Dora; Vioque, Jesús; Alonso-Gómez, Ángel M.; Wärnberg, Julia; Martínez, José A.; et al. (Frontiers in Endocrinology, 2021)
INTRODUCTION: Type 2 diabetes has been linked to greater cognitive decline, but other glycemic parameters such as prediabetes, diabetes control and treatment, and HOMA-IR and HbA1c diabetes-related biomarkers have shown inconsistent results. Furthermore, there is limited research assessing these relationships in short-term studies. Thus, we aimed to examine 2-year associations between baseline diabetes/glycemic status and changes in cognitive function in older participants at high risk of cardiovascular disease. METHODS: We conducted a 2-year prospective cohort study (n=6,874) within the framework of the PREDIMED-Plus study. The participants (with overweight/obesity and metabolic syndrome; mean age 64.9 years; 48.5% women) completed a battery of 8 cognitive tests, and a global cognitive function Z-score (GCF) was estimated. At baseline, participants were categorized by diabetes status (no-diabetes, prediabetes, and <5 or ≥5-year diabetes duration), and also by diabetes control. Furthermore, insulin resistance (HOMA-IR) and glycated hemoglobin (HbA1c) levels were measured, and antidiabetic medications were recorded. Linear and logistic regression models, adjusted by potential confounders, were fitted to assess associations between glycemic status and changes in cognitive function. RESULTS: Prediabetes status was unrelated to cognitive decline. However, compared to participants without diabetes, those with ≥5-year diabetes duration had greater reductions in GCF (β=-0.11 [95%CI -0.16;-0.06]), as well as in processing speed and executive function measurements. Inverse associations were observed between baseline HOMA-IR and changes in GCF (β=-0.0094 [95%CI -0.0164;-0.0023]), but also between HbA1c levels and changes in GCF (β=-0.0085 [95%CI (-0.0115, -0.0055]), the Mini-Mental State Examination, and other executive function tests. Poor diabetes control was inversely associated with phonologic fluency. The use of insulin treatment was inversely related to cognitive function as measured by the GCF (β=-0.31 [95%CI -0.44, -0.18]), and other cognitive tests. CONCLUSIONS: Insulin resistance, diabetes status, longer diabetes duration, poor glycemic control, and insulin treatment were associated with worsening cognitive function changes in the short term in a population at high cardiovascular risk.